Верховинця степова криниця - Верховинець, Я. (Народна творчість та етнографія, 2006)
У вересні 2005 року у місті Нова Каховка Херсонської області відбувся Другий Всеукраїнський хореографічний фестиваль-конкурс "Верховинця степова криниця", присвячений 125-й річниці від дня народження Василя Миколайовича Верховинця. In September of 2005 in the town of New Kakhovka occurred Second Ukrainian Choreography Festival “The Steppe Well of Verkhovynets", dedicated to the 125th Anniversary of Vasy! Verkhovynets, who was an Ukrainian composer, folklorist, who did a lot in a field of recording of the folk dance and the study of folk choreography.